Perancangan Ulang Interior Perpustakaan Putri Pondok Pesantren Modern Islam Assalaam Sukoharjo Dengan Pendekatan Psikologi Ruang - Faila Syifa, Andini; Liritantri, Widyanesti; Laksitarini, Niken (Telkom University, 2024)
In this rapidly developing era, libraries play a crucial role in seeking information and knowledge from various sources, given the significant changes brought about by technology in society. To attract students, libraries are required to keep up with the times by providing good and comprehensive facilities and appealing interiors. Comprehensive facilities encourage students to visit the library. The redesign aims to address existing issues and maintain the quality and functionality of library spaces, providing users with a better learning experience and creating a visual identity to enhance institutional image. Data collection methods include distributing questionnaires to respondents, conducting interviews with library managers, surveys, and benchmarking studies. Additionally, literature is sought through the internet, journals, guidebooks, and articles for design references. Keywords: library; interior; facilities